Myocardial function during chronic food restriction in isolated hypertrophied cardiac muscle - Cicogna, A. C. [UNESP]; Padovani, C. R. [UNESP]; Okoshi, K. [UNESP]; Aragon, F. F. [UNESP]; Okoshi, M. P. [UNESP] (Elsevier, 2000)
Background: The effect of food restriction (FR) on myocardial performance has been studied in normal hearts. Few experiments analyzed the effects of undernutrition on hearts subjected to cardiac overload. The aim of this study was to determine whether chronic FR promotes more significant changes in hypertrophied hearts than in normal hearts. Methods: Myocardial performance was studied in isolated left ventricular papillary muscle from young male spontaneously hypertensive rats (SHR) and age-matched normotensive Wistar-Kyoto rats (WKY) submitted to FR or to control diet. The animals subjected to FR were fed 50% of the amount of food consumed by control groups for 60 days. Isolated muscles were studied while contracting isometrically and isotonically. Results: FR decreased the body weight and the left ventricular weight in both groups. FR increased the left ventricular weight-to-body weight ratio in the WKY rats and tended to decrease this ratio in SHR (P = 0.055). The arterial systolic pressure was greater in SHR than in WKY groups and did not change with FR. In the animals with normal diet, myocardial performance was better in SHR than in WKY. FR increased time to tension to fall from peak to 50% of peak tension and time to peak tension in the WKY rats and time to peak tension in the SHR. Conclusions: FR for 60 days has a trend to attenuate the development of cardiac hypertrophy and does not promote more mechanical functional changes in the hypertrophied myocardium than in the normal cardiac muscle.
Keywords: Cardiac hypertrophy; Diet; Isolated papillary muscle; Spontaneously hypertensive rat (SHR)